An overview of employee retention strategies & its impact on turnover of the employees - PC, Dr. Neena; N, Dr. Dinesh; Bhat, Dr. Vinayak Anil (The journal of contemporary issues in business and government, 2023)
Employees are the most valuable asset for an organisation’s success. Employee retention is a process where the organisation retains their existing employees for a maximum period of time or until a project is completed. This research paper focuses on what are the strategies used by the organisation to retain their employee, how effective is these strategies to retain their employees. The management has to consider the retention of their employees as a top priority, and hence, studying various factors such as work-life balance policies, work environment, proper recognition and reward, career growth, training & development, social interaction & support, compensation and other benefits are very crucial to examine the relationship between employee retention strategies and the employee turnover. The research paper analysed about how these factors of various retention strategies will have a positive or negative impact on the employee’s turnover. The key findings of the study demonstrated on the most relevant strategies opted by the organizations, which will have a positive and negative impact on their employees which will lead to employee turnover.